2020
DOI: 10.1039/d0en00507j
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and structural characterization of SeIV biotransformations by Stenotrophomonas bentonitica into Se0 nanostructures and volatiles Se species

Abstract: Microorganisms such as Stenotrophomonas bentonitica could influence the safety of the deep geological repository system by producing nanoparticles and volatile compounds of selenium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 61 publications
3
38
0
Order By: Relevance
“…The first Se-Se coordination shell at a bond distance of 2.35 A reflected an amorphous nature of the nanoparticles, while the second Se-Se shell at 3.69 A suggested their crystalline structure. Similar results were obtained for selenium nanoparticles produced by S. bentonitica (Ruiz-Fresneda et al, 2020). They found two Se-Se coordination shell that would correspond to amorphous and trigonal Se, and suggested, with the help of other techniques, a transformation process from amorphous to trigonal selenium.…”
Section: X-ray Absorption Spectroscopy (Xas)supporting
confidence: 78%
See 1 more Smart Citation
“…The first Se-Se coordination shell at a bond distance of 2.35 A reflected an amorphous nature of the nanoparticles, while the second Se-Se shell at 3.69 A suggested their crystalline structure. Similar results were obtained for selenium nanoparticles produced by S. bentonitica (Ruiz-Fresneda et al, 2020). They found two Se-Se coordination shell that would correspond to amorphous and trigonal Se, and suggested, with the help of other techniques, a transformation process from amorphous to trigonal selenium.…”
Section: X-ray Absorption Spectroscopy (Xas)supporting
confidence: 78%
“…This technique may also be used to investigate the nature of organic matter (proteins, lipids, polysaccharides, etc.) attached to biogenic nanoparticles of interest (Eswayah et al, 2019;Fischer et al, 2020;Ruiz-Fresneda et al, 2020), which could affect their interactions and hence their environmental fate. For instance, the presence of absorption bands at 1659 and 1538 cm -1 corresponding to C-O, N- H and C-N vibrations attributed to amide I and amide II groups in purified selenium nanoparticles from Stenotrophomonas bentonitica suggested the presence of proteins surrounding them (Ruiz-Fresneda et al, 2020).…”
Section: Fourier Transform Infrared (Ftir) Spectroscopymentioning
confidence: 99%
“…From quantitative XPS, it could be estimated that a skin of mixed Ge oxides of ≈(0.3±0.1) nm is present after this short‐term exposure to air. Se 3d also displays a new component at high BE (55.1 eV) associated with the formation of elemental Se, [ 29 ] which was not visible after O 2 and H 2 O dosage in UHV conditions. For longer air exposure, the intensity of Ge 2 Se 3 –GeSeO x as well as that of intermediate oxide components (GeO, Ge 2 O 3 , and Ge 3 O 4 ) increases, and after 30 h in air a new feature at 32.7 eV appears (≈9% of the total Ge3d area), which can be ascribed to the formation of GeO 2 (Ge 4+ ).…”
Section: Resultsmentioning
confidence: 99%
“…In Se-DG-6, the (110) plane corresponding to 0.218 nm t-Se was also noticed. 17,18 Therefore, it was concluded that upon increase of the Se% in the Se-DGs, discrete lattice fringes appear more prominently in the SAED pattern.…”
Section: Characterizationmentioning
confidence: 98%
“…Analysis of the high-magnification (5 nm and 10 nm) HRTEM images Catalysis Science & Technology Paper confirmed the presence of Se-NPs from the distinct lattice fringes (marked with yellow lines, using ImageJ software) with d-spacing values of 0.372 ± 0.002 nm (100 plane), 0.284 ± 0.002 nm (101 plane) and 0.215 ± 0.005 nm (110 plane), which were present in trigonal Se crystal (t-Se) form. 17 Amorphous lattice fringes of graphitic sheets having a d-spacing value 0.380 ± 0.003 nm (002 plane) were also found around the edges. 18 From the selected area electron diffraction (SAED) patterns (Fig.…”
Section: Characterizationmentioning
confidence: 98%